Preparation and Phase Relations in the CuSbSe2 – CuInSe2 System. Issue 1735 (31st May 2016) - Korzun, Barys V.; Sobol, Valery R.; Rusu, Marin; Savizky, Ruben M.; Fadzeyeva, Alena A.; Maroz, Ivan I.; Gavrilenko, Andrei N.; Matukhin, Vadim L.; Lux-Steiner, Martha Ch.
ABSTRACT: The CuInSe2 and CuSbSe2 ternary compounds and alloys of the (CuSbSe2 )1-x ·(CuInSe2 )x system with the mole fraction of CuInSe2 (x) equal to 0.05, 0.15, 0.25, 0.375, 0.50, 0.625, 0.75, 0.85, and 0.95 were prepared and the phase relations in this system were investigated by X-ray powder diffraction, optical microscopy, and scanning electron microscopy. It was shown that the alloys of the CuSbSe2 -CuInSe2 system are biphasic at room temperature in the whole range of compositions, and the limits of solubility for CuSbSe2 in CuInSe2 and for CuInSe2 in CuSbSe2 do not exceed 0.001 mole fraction.